Translating and Performing Psalm 133 Using Oral Bible Translation and Local Genres - Cleaver, Bronwen (The Bible translator, 2025)
This article encourages translators to research and analyse local genres to help achieve a quality translation, offering a case study from Siberia: the Altai people’s experience translating Psalm 133 in a sung poetic form. It examines different ways of ensuring quality throughout that process.